Initial experiences of a student assistantship. (27th May 2015) - Fullbrook, Alexander; Ross, Michael; Mellanby, Ed; Wylde, Keith; Jaap, Alan; Cameron, Helen
Summary Background Evidence suggests that medical graduates are underprepared to work as junior doctors. To ease transition in the UK, the General Medical Council (GMC) recommended the introduction of a student 'assistantship'. This is a period of training where final‐year students take on duties of a foundation doctor under supervision. This study explored the experiences of the first cohort of students and junior doctors participating in the assistantship in one UK medical school in 2012. Methods All 248 students and their supervisors were asked to complete an online feedback questionnaire. All students who went on to work locally were also invited to participate in focus groups as recent graduates. <boxed-text content-type="pullQuote" position="anchor" orientation="portrait"> Evidence suggests that medical graduates are underprepared to work as junior doctors </boxed-text> Results Questionnaire response rates were 49 per cent for students and 43 per cent for supervisors. Fifteen new graduates participated in focus groups. Aspects of the assistantship considered important to participants frequently mapped to areas specified by the GMC and the locally identified learning outcomes. Additional themes identified included the importance of having meaningful responsibility for patient care, a placement in a general medical or surgical ward and receiving effective feedback. Discussion The assistantship seems to have been highly valued by students, but could be improved by ensuring that all students are given relevant placements and clinical responsibility.